2013
DOI: 10.14573/altex.2013.3.293
|View full text |Cite
|
Sign up to set email alerts
|

In vitro pituitary and thyroid cell proliferation assays and their relevance as alternatives to animal testing

Abstract: Summary This study investigates the in vitro effect of eleven thyroid-active compounds known to affect pituitary and/or thyroid weights in vivo, using the proliferation of GH3 rat pituitary cells in the so-called "T-screen," and of FRTL-5 rat thyroid cells in a newly developed test denoted "TSH-screen" to gain insight into the relative value of these in vitro proliferation tests for an integrated testing strategy (ITS) for thyroid activity. Pituitary cell proliferation in the T-screen was stimulated by three o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…In the following we use the H, M, L abbreviations to state high, medium and low concentrations, respectively. The chosen concentrations are in or below the range of the doses tested in immortalized thyrocytes for ETU17 and other cell systems for CPF18. Since humans are usually co-exposed, we also treated the cells with the mixtures of ETU and CPF to evaluate possible additive/synergic effects.…”
Section: Resultsmentioning
confidence: 99%
“…In the following we use the H, M, L abbreviations to state high, medium and low concentrations, respectively. The chosen concentrations are in or below the range of the doses tested in immortalized thyrocytes for ETU17 and other cell systems for CPF18. Since humans are usually co-exposed, we also treated the cells with the mixtures of ETU and CPF to evaluate possible additive/synergic effects.…”
Section: Resultsmentioning
confidence: 99%
“…the pathways involved in human thyroid development are conserved in the zebrafish and so are its tissue architecture, function and feedback regulation by the HPt axis, making it a promising model for the study of thyroid-active compounds (Bourque and Houvras, 2011;Jomaa et al, 2013;Raldúa and Babin, 2009). …”
Section: Fig 5: T3 Ptu MMI and Naclo 4 -Induced Alterations In Devmentioning
confidence: 99%
“…Substances that are marketed or manufactured in quantities above 100 tons per annum are required to be tested for pre-natal developmental toxicity (OeCD 414) (ReACH, 2006). Based on data on chemical production from 1991 to 1994, the eU estimates that 2.6 million animals will be needed for all ReACH testing or a total of 9 million when offspring produced during reproductive and developmental toxicity test-weights used as endpoints in in vivo assays (Jomaa et al, 2013). While the effect of estrogen-mimicking compounds on cell proliferation in the in vitro e-screen was found to correlate with their effects on in vivo uterine weight (r 2 =0.85) , the effects of thyroid-active compounds on thyroid (tSHscreen) and pituitary (t-screen) cell proliferation was found to have poor correlation with their effects on the weight of these respective organs in vivo.…”
mentioning
confidence: 99%
“…While it is currently not possible to replicate thyroid histopathology in vitro, in a previous study we have searched for potential correlation between the effects of chemicals on pituitary and thyroid organ weights in vivo and the effects of the same set of chemicals on cellular proliferation in vitro using pituitary and thyroid model cell lines. To this end, 11 thyroid-active compounds were tested and it was concluded that in vitro cellular proliferation alone correlates poorly with pituitary and thyroid organ weight change in vivo (Jomaa et al, 2013). This is likely due to the complex multi-organ paradigm that the thyroid system represents (Jomaa, 2014).…”
Section: Introductionmentioning
confidence: 99%